EXTRALINGUISTIC DETERMINATION OF SUBJECT-PREDICATE AGREEMENT - Irina N. Morozova (Вестник Северо-Кавказского федерального университета)
The article is devoted to experimental study of subject-predicate agreement in structures with either…or… / neither…nor… conjunctions in the English language. Great attention is paid to extralinguistic factors of predicate alternation.